The effect of paper surface-coating pigments and binders on colour gamut and printing parameters - ÖZCAN, ARİF; TUTAK, DOĞAN (WILEY, 2021)
One of the most important factors affecting the printing quality of printing processes is the surface structure of the printing material. The surface structure of the paper formed by fibres can be modified and smoothed out using coatings that make it more suitable for printing. In this study, three different types of coating pigments were prepared and applied onto an 80 g/m(2) base paper surface. Styrene butadiene latex and polyvinyl alcohol were used as binders, and three different types of pigments, precipitated calcium carbonate, clay and zeolite, were used as pigments in the prepared coatings. The physical and optical properties of all calendered and non-calendered papers were measured and compared. All the prints were produced with an ink-jet digital printing machine upon the coated and calendered papers for recording the printability parameters. The Delta E-00 differences between colours, tone values, colour gamuts and colour gamut volumes were measured from the surfaces of the printed papers. The results showed that the coating type had a better effect on print quality, and that the printability properties of coated papers and even calendered papers were very good.